2016
DOI: 10.1016/j.beproc.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the persistence of a heterogeneous behavior chain: Studies of extinction in a rat model of search behavior of working dogs

Abstract: Dogs trained to search for contraband perform a chain of behavior in which they first search for a target and then make a separate response that indicates to the trainer that they have found one. The dogs often conduct multiple searches without encountering a target and receiving the reinforcer (i.e., no contraband is present). Understanding extinction (i.e., the decline in work rate when reinforcers are no longer encountered) may assist in training dogs to work in conditions where targets are rare. We therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 26 publications
4
22
0
Order By: Relevance
“…This highlights the importance of ongoing training in maintaining a well-functioning working animal (e.g. [19, 20]) and suggests the importance of appropriate selection and training of clients, as well as dogs.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the importance of ongoing training in maintaining a well-functioning working animal (e.g. [19, 20]) and suggests the importance of appropriate selection and training of clients, as well as dogs.…”
Section: Discussionmentioning
confidence: 99%
“…A long tradition of research on resistance to extinction of simple Pavlovian and instrumental responses suggests that training that involves nonreinforcement will translate to greater persistence during extinction (Capaldi, 1966, 1994). Likewise, training that increased the number of nonreinforced procurement responses led to slower extinction of procurement (Thrailkill, Kacelnik, et al, 2016). Another way to increase generalization is to continue to present stimuli from training during extinction.…”
Section: Discussionmentioning
confidence: 99%
“…The results (Figure 3b) clearly suggest that extinction of S1R1 was slower in the group tested with noncontingent pellets (P) than the group tested without (NP). It is notable that in another experiment we found that introducing noncontingent reinforcers for the first time during S1R1 extinction reduced S1R1 responding, presumably by creating generalization decrement (Thrailkill et al, 2016, Experiment 2). Therefore, presenting the noncontingent pellets during training and delivering them in the ITI were each important for enhancing the persistence of S1R1 in extinction.…”
Section: Persistence Of Chained Behaviorsmentioning
confidence: 93%
See 2 more Smart Citations